2011
DOI: 10.1007/s10815-011-9589-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mullerian hormone as a predictive marker for the selection of women for oocyte in vitro maturation treatment

Abstract: Purpose In oocyte in-vitro maturation (IVM) treatments, the chances to achieve a pregnancy are critically dependent on the retrieval of a suitable number of oocytes. In this study, we assessed the ability of circulating levels of anti-mullerian hormone (AMH) to identify normo-ovulatory women suitable for IVM treatment on the basis of the number of retrieved oocytes. Method Serum AMH was quantified in normo-ovulatory women younger than 39 years undergoing IVM treatment. After immature oocyte retrieval and IVM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 62 publications
(88 reference statements)
4
17
0
Order By: Relevance
“…Our findings are in agreement with Fadini et al [8] who also showed a correlation between AMH levels and the number of oocytes harvested, The final number of matured oocytes suitable for fertilization is dependent not only on their quantity but also upon their quality and maturation potential in in vitro culture systems. In this respect, our study reports for the first time to the best of our knowledge the association between AMH levels and the maturational status of oocytes, where on the day of the OPU, we did not detect any correlation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in agreement with Fadini et al [8] who also showed a correlation between AMH levels and the number of oocytes harvested, The final number of matured oocytes suitable for fertilization is dependent not only on their quantity but also upon their quality and maturation potential in in vitro culture systems. In this respect, our study reports for the first time to the best of our knowledge the association between AMH levels and the maturational status of oocytes, where on the day of the OPU, we did not detect any correlation.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have also shown that in IVM cycles, the number of available oocytes is the single most important factor correlating with a successful procedural outcome in NO patients [5,8,9]. Our findings are in agreement with Fadini et al [8] who also showed a correlation between AMH levels and the number of oocytes harvested, The final number of matured oocytes suitable for fertilization is dependent not only on their quantity but also upon their quality and maturation potential in in vitro culture systems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Motivated by the experience gained over years of clinical practice in IVM [10][11][12][13], in the present study we aimed to compare not IVM with standard IVF-COS as clinical approaches, but rather to evaluate the relative competence of oocytes matured in vivo recovered from follicles of different developmental stages. Pursuing this objective, oocytes matured in vivo retrieved from antral follicles in IVM cycles were analyzed together with oocytes normally recovered from preovulatory follicles following conventional IVF-COS in order to assess comparatively their ability of establishing a viable pregnancy.…”
Section: Introductionmentioning
confidence: 99%